Seleção de genótipos de eucalyptus para produção de painéis compensados - Rocha, Gabriel Costa (Universidade Federal do Tocantins, 2018)
Selection of Eucalyptus genotypes for the production of compensated panels. This work aimed to select genetic material of Eucalyptus spp. for the production of compensated panels and to evaluate the quality of the wood of panels made from Eucalyptus slides, combined with Pinus and virola, in order to obtain information on the potential of the evaluated material. For the research, a clonal test was installed in the randomized complete block design, consisting of 29 clones and six replications, totaling 174 plots with six plants each, spaced 3 m x 3 m. The border was made in double row with Eucalyptus dunnii material. The silvicultural characteristics diameter at breast height (DBH), total plant height (ALT) and volume of wood (VOL) were evaluated at 48 months after planting. The genetic parameters were estimated based on the statistical procedure REML/BLUP. After the panels were made, the wood quality tests were performed, evaluating the physical properties (moisture content and basic density) and mechanical properties (shearing, parallel bending and perpendicular bending) of the panels. Significant genetic variations were observed among the clones, for the silvicultural characters evaluated in the environmental conditions of the experiment, being possible to obtain gains by selection. Five of the clones evaluated had potential to be used in the breeding program of the company and in commercial plantations of the region where the municipality of Palma Sola - SC is located. The best performing clone was USP/IPEF 68 (E. dunnii), with values above almost all criteria. The panels produced with Pinus core and virola, where, in these cases, only the cover and the back cover were Eucalyptus slides, presented good performance when compared to panels consisting exclusively of Eucalyptus slides. The panels with the virola core, the perpendicular flexion test, and those with the Pinus core were tested in the parallel flexure test. The panels constituted 100% of Eucalyptus did not contribute to the significant increase in the MOE and MOR values parallel and perpendicular. However, the values were higher in more promising clones, such as USP/IPEF 68 and USP/IPEF 64. The results of the glue line resistance and parallel and perpendicular static flexion obtained in this study are adequate to the standards used. It is concluded, therefore, that USP/IPEF 68 (E. dunnii) material is recommended for the manufacture of plywood panels due to their inherent qualities in wood.